Concomitant Idiopathic Intracranial Hypertension, Normal Pressure Hydrocephalus, and Pleomorphic Xanthoastrocytoma: A Case Report and Review of the Literature. (2nd September 2020) - Alhussinan, Modhi; Elarjani, Turki; Jawharri, Mohammed; Albrahim, Mohammed; Farrash, Faisal
Abstract : Background . Idiopathic intracranial hypertension (IIH) and normal pressure hydrocephalus (NPH) are disorders of the cerebrospinal fluid (CSF) flow dynamics. Pleomorphic xanthoastrocytoma (PXA) is a rare low-grade astrocytoma (World Health Organization grade II) representing <1% of astrocytomas. Combination of IIH and NPH with PXA is unheard of, with few published cases discussing the association of CNS tumors with either IIH or NPH, but never combined. We present a case of a 51-year-old woman with such a rare combination. Case Presentation . A fifty-one-year-old obese female presented with a progressive visual loss, abducens nerve palsy, and headache for three months. Further investigations revealed a right frontal tumor and ventriculomegaly on magnetic resonance imaging. Her symptoms improved remarkably after total surgical excision of the tumor with a ventriculoperitoneal (VP) shunt. Conclusion . The pathophysiology behind NPH and IIH is still not fully understood, yet their management is mostly dependent on CSF diversion. The concomitant development of two different CSF dynamic diseases with a PXA has not been reported in the literature. We hypothesize that PXA may have sparked an abnormal CSF circulation pattern and ventriculomegaly.